2002
DOI: 10.1093/ije/31.1.210
|View full text |Cite
|
Sign up to set email alerts
|

Brain cancer and occupational exposure to magnetic fields among men: results from a Canadian population-based case-control study

Abstract: Our findings support the hypothesis that occupational magnetic field exposure increases the risk of glioblastoma multiforme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 32 publications
3
38
0
7
Order By: Relevance
“…Electrical fields are much more effectively shielded by the dielectric properties of water-rich tissues than MFs. An analysis of five recent studies has demonstrated a modest increase of risk for leukemia and brain cancer in electric utility workers from France, Canada, and the United States (36,70,85). Furthermore, a list of suspected field-induced cancer types including male breast cancer and malignant melanoma has been put forward (66).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 99%
“…Electrical fields are much more effectively shielded by the dielectric properties of water-rich tissues than MFs. An analysis of five recent studies has demonstrated a modest increase of risk for leukemia and brain cancer in electric utility workers from France, Canada, and the United States (36,70,85). Furthermore, a list of suspected field-induced cancer types including male breast cancer and malignant melanoma has been put forward (66).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 99%
“…A Canadian study suggested that the risk association could be stronger for more aggressive forms, which was judged consistent with the hypothesis that magnetic fields act at the promotional stage. 17 If so, the risk we found in our study could be underestimated.…”
Section: Discussionmentioning
confidence: 67%
“…Too few studies have presented results for histologic subtypes of brain cancer to draw firm conclusions, although some have shown stronger associations with gliomas 3 , and a more recent study reported a more pronounced risk for glioblastoma multiforme. 26 In conclusion, in our population-based, nested case-control study, we found moderately elevated ORs for exposure to residential magnetic fields and brain tumours but no clear exposureresponse pattern. The results, however, are not consistent with our findings for occupational exposure, where the analysis showed an inverse association.…”
mentioning
confidence: 51%